2008
DOI: 10.1097/iop.0b013e318183267a
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Canalicular Lacerations

Abstract: Direct, indirect, or diffuse forces may injure canaliculi but direct penetrating injuries were more common than avulsive injuries. More serious injuries (orbital fractures, globe rupture, other body injuries, and head trauma) were more commonly seen when diffuse trauma was involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 6 publications
4
48
2
9
Order By: Relevance
“…Jordan et al [5] found inferior laceration in 50%, superior laceration in 23%, and bicanalicular laceration in 4% of cases. In the present study, percentage of inferior canalicular injury cases was 83% (n=34), whereas superior canaliculus was site of trauma in 17% (n=7).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Jordan et al [5] found inferior laceration in 50%, superior laceration in 23%, and bicanalicular laceration in 4% of cases. In the present study, percentage of inferior canalicular injury cases was 83% (n=34), whereas superior canaliculus was site of trauma in 17% (n=7).…”
Section: Discussionmentioning
confidence: 99%
“…Jordan et al reported that direct injury was responsible for laceration in more than half (54%) of cases. [5] In 25-case review conducted by Wulc et al, they reported 84% avulsive injury and 16% direct injury. [6] In the present study, too, avulsive injury was observed in majority of the patients; however, it seems that this classification is not used in many series regarding canalicular laceration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tek kanalikül yaralanması daha sık görülmekte ve alt kanalikül, üst kanaliküle göre daha sık yaralanmaktadır. [5][6][7] Lakrimal boşaltım sistemi künt veya kesici travmalar sonucunda yaralanabilir. Literatürde indirekt travmaların direkt kesici travmalardan daha sık olduğu ifade edilmektedir.…”
Section: Introductionunclassified